A Provisional Mix Design of Porous Asphalt Pavement Using Crumb Rubber Modified Bituminous Mixes - Rajesh Kumar K. (E3S Web of Conferences)
Porous asphalt pavements are typically used in parking lots that allow the drainage of water through the pavement surface, enabling it to permeate into a stone recharge bed and subsequently enter the underlying soils. The current study aims to utilise Crumb Rubber (mesh 40) together with Bitumen using a wet procedure to create Crumb rubber modified bitumen (CRMB). The Marshall Stability method was employed to conduct bituminous mix design tests on different proportions of CR (crumb rubber) at 8%, 10%, and 12% relative to the total weight of the bitumen. The objective was to assess the mix design features. The aims of the research were to develop a method for designing a porous asphalt mix using the recommended gradation by the National Centre for Asphalt Technology (NCAT) and locally sourced aggregates. Additionally, the study aimed to determine the optimal binder content by employing the Open-Graded Friction Course (OGFC) design concept. Furthermore, the research sought to assess the laboratory performance of the mix in terms of Marshall Stability. Furthermore, it is important to formulate a preliminary set of criteria for the mix design of Porous Asphalt that possesses sufficient permeability and durability to withstand large traffic loads in the specific climatic conditions prevalent in India.